2017
DOI: 10.1007/s00428-017-2207-y
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic small round cell tumor: evaluation of reverse transcription-polymerase chain reaction and fluorescence in situ hybridization as ancillary molecular diagnostic techniques

Abstract: Desmoplastic small round cell tumor (DSRCT) is a rare, biologically aggressive soft tissue neoplasm of uncertain differentiation, most often arising in the abdominal and pelvic cavities of adolescents and young adults with a striking male predominance. Histologically, it is characterized by islands of uniform small round cells in prominent desmoplastic stroma, and it has a polyimmunophenotypic profile, typically expressing WT1 and cytokeratin, desmin, and neural/neuroendocrine differentiation markers to varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…However, the fusion assay did not detect EWSR1-WT1 fusion, a near universal finding in DSRCTs. 18 Furthermore, in contrast to DSRCTs, these tumors expressed myoD1 and myogenin and did not express epithelial markers. DSRCTs, occasionally express CD99, although the reactivity is cytoplasmic and not membranous, as noted in the current two cases.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the fusion assay did not detect EWSR1-WT1 fusion, a near universal finding in DSRCTs. 18 Furthermore, in contrast to DSRCTs, these tumors expressed myoD1 and myogenin and did not express epithelial markers. DSRCTs, occasionally express CD99, although the reactivity is cytoplasmic and not membranous, as noted in the current two cases.…”
Section: Discussionmentioning
confidence: 89%
“…31,32 Notably DSRCT, characterized by EWSR1-WT1 fusion, also shows polyphenotypic differentiation with expression of keratins, EMA, vimentin, desmin, CD57 and S100. 18 Although the precise mechanism for this phenomenon is unknown, the chimeric EWSR1-WT1 protein transcript activates neural reprogramming factor ASCL1, accounting for neural differentiation. 33 Activation of transcriptional factors along multiple lineages might thus be responsible for polyphenotypic differentiation in DSRCT and, by extension, the EWSR1-PATZ1 fusion positive sarcoma.…”
Section: -26mentioning
confidence: 99%
“…DSRCT is distinguished by the t (11;22) (p13; q12) chromosomal translocation involving a fusion between the transcriptional activating domain of EWSR1 and the WT1 gene [19][20][21]. Studies have also suggested that the EWSR1-WT1 fusion protein can induce the expression of PDGFA.…”
Section: Discussionmentioning
confidence: 99%
“…The multi-fold genome coverage allows the MinION nanopore sequencing to reach over 99% accuracy of the post-data analysis, which is sufficient for accurate detection of known viruses ( Wang et al, 2015 ). This technology was successfully used for detection of multiple arboviruses including DENV, ZIKV, and Venezuelan Equine Encephalitis Virus ( Mohamed et al, 2017 ; Quick et al, 2017 ; Russell et al, 2018 ).…”
Section: Challenges Of Zikv Diagnostics and Treatmentmentioning
confidence: 99%